Answer:
s[1] = 0.2; s[n] = -5·s[n-1]
Explanation:
To write a recursive formula, you need to know how a given term relates to the ones before it. Here, each term is -5 times the one before. So part of the formula is ...
s[n] = -5·s[n-1]
The other part of a recursive formula is the part that tells the initial values necessary to make this recursive function work. Here, one initial value is needed. We know that the first term is 0.2, so that's what we need to say:
s[1] = 0.2
__
The recursive formula is ...
- s[1] = 0.2
- s[n] = -5·s[n-1]